2021
DOI: 10.1016/j.isci.2021.103524
|View full text |Cite
|
Sign up to set email alerts
|

Closantel is an allosteric inhibitor of human Taspase1

Abstract: Dimerization of Taspase1 activates an intrinsic serine protease function that leads to the catalytic Thr234 residue, which allows to catalyze the consensus sequence Q À3 X À2 D À1 ,G 1 X 2 D 3 D 4 , present in Trithorax family members and TFIIA. Noteworthy, Taspase1 performs only a single hydrolytic step on substrate proteins, which makes it impossible to screen for inhibitors in a classical screening approach. Here, we report the development of an HTRF reporter assay that allowed the identification of an inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…It highlights the significance of CLO in controlling the global spread of plasmid-mediated CST resistance. More recent studies have identified CLO as a novel allosteric inhibitor of human Taspase1 (Luciano et al, 2021). All these reports show the importance of reuse old drugs under the circumstances that the development of new drugs is becoming more and more difficult.…”
Section: Open Accessmentioning
confidence: 99%
“…It highlights the significance of CLO in controlling the global spread of plasmid-mediated CST resistance. More recent studies have identified CLO as a novel allosteric inhibitor of human Taspase1 (Luciano et al, 2021). All these reports show the importance of reuse old drugs under the circumstances that the development of new drugs is becoming more and more difficult.…”
Section: Open Accessmentioning
confidence: 99%